FAKTOR YANG MEMPENGARUHI PROMOSI DAN INFORMASI WISATA PULAU CINTA: Pulau Cinta, SEM, Proposisi, Informasi - sukri sukri; Widya Rahmalina (LPPM Universitas Abdurrab, 2019)
The tourism sector is a sector that has the potential to be developed as a business of local revenues, the program of development and utilization of resources and regional tourism potential is expected to contribute to economic development. One of the tours that can support the regional economy in Riau is Cinta Island, which is located in the Jering Bay Village, Tambang District, Kampar Regency. The number of visitors to Pulau Cinta reaches 9000 people every month. To maintain the number of visits with the achievement of the desired target, it is necessary to analyze factors that influence promotion and information so that visitors still visit the island of love. Promotion and information are factors that will be an important role and support for adding visitors to Cinta Island. Thus, the Structure Equation Modeling (SEM) model can be used to determine the factors that influence promotion and information that are featured on the island of Cinta. The results showed that the SEM model that was built could be accepted because it fulfilled several model feasibility tests stating that the model was good-fit. The results of hypothesis testing show that attractiveness factors such as natural beauty and cleanliness and supporting factors in the form of facilities and infrastructure have a positive effect on promotion and information. While the factors of safety, accessibility, and infrastructure deserve the attention of tourism managers.